Most Common Publication Types of Neuroimaging Literature: Papers With High Levels of Evidence Are on the Rise - Yeung, Andy Wai Kan (Frontiers in Human Neuroscience, 2020)
Objective: This study evaluated the bibliometric data of the most common publication types of the neuroimaging literature. Methods: PubMed was searched to identify all published papers with “neuroimaging” as their MeSH Major Topics, and they were further searched by the following publication types: case report, clinical trial, comparative study, editorial, evaluation study, guideline, meta-analysis, multicenter study, randomized controlled trial, review, technical report, and validation study. The proportion of papers belonging to each publication type published in neuroimaging journals was calculated. Year-adjusted mean citation counts for each publication type were computed using data from Web of Science. Publication trend, and its correlation with citation performance, were assessed. Results: Review and comparative study were the most common publication types. Publication types with the highest proportion in neuroimaging journals were guideline, validation study, and technical reports. Since year 2000, multicenter study, review, and meta-analysis showed the strongest linear increase in annual publication count. These publication types also had the highest year-adjusted citation counts (4.7 to 10.0). Publication types with lowest year-adjusted citation counts were editorial and case report (0.5 to 1.0). It was estimated that 12.5% of the publications labeled as case reports were incorrectly labeled. Conclusions: Neuroimaging literature has been expanding with papers of higher levels of evidence, such as meta-analyses, multicenter studies, and randomized controlled trial.